1998
DOI: 10.1002/(sici)1521-3773(19981116)37:21<3036::aid-anie3036>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrochemistry, and Spectroscopy of Blue Platinum(II) Polyynes and Diynes

Abstract: The smallest band gap observed so far (1.77 eV) for an organometallic polymer is exhibited by the blue, rigid-rod polymer 2, which is prepared by the reaction of trans-[PtCl (PnBu ) ] with one equivalent of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 2 publications
9
95
1
Order By: Relevance
“…Platinum r-acetylides 3 and 4 also displayed an irreversible oxidation wave at about 0.68 V corresponding to the one-electron oxidation of the platinum residue. Similar anodic waves were also observed for trans-[Pt(C3C-p-C 6 H 4 C3CH)(PEt 3 ) 2 (Ph)] [18] and trans-[Pt(C 6 H 4 -p-CH 3 )(C3C-p-C 6 H 5 )(PPh 3 ) 2 ]. [24] The UV/VIS absorption spectra of 1 and 2 essentially consist of ligand-localized p-p* transitions in the near UV (ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum r-acetylides 3 and 4 also displayed an irreversible oxidation wave at about 0.68 V corresponding to the one-electron oxidation of the platinum residue. Similar anodic waves were also observed for trans-[Pt(C3C-p-C 6 H 4 C3CH)(PEt 3 ) 2 (Ph)] [18] and trans-[Pt(C 6 H 4 -p-CH 3 )(C3C-p-C 6 H 5 )(PPh 3 ) 2 ]. [24] The UV/VIS absorption spectra of 1 and 2 essentially consist of ligand-localized p-p* transitions in the near UV (ca.…”
Section: Resultsmentioning
confidence: 99%
“…[14,15] It has been demonstrated that the introduction of electron-withdrawing or electron-donating substituents into the conjugated system is an important tool for bandgap control. [16,17] Illustrative examples include the novel platinum (II) polyyne polymers incorporating the electron-deficient thieno [3,4b]pyrazine (1.8 eV) [18] or the electron-rich ferrocenylfluorene (2.1 eV) unit. [19] In order to design narrow-bandgap organometallic polyynes, we make use of a 9-dicyanomethylene-substituted fluorene as an electron acceptor on the grounds that they are widely used in the investigation of electron donor/acceptor interaction in charge-transfer complex formation, activation of photoconductivity of organic semiconductors and as electron transport materials.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we have described photoconductive and photovoltaic properties in solid-state devices made with PFS/fullerene composite thin films. [38] Although some platinum-or ruthenium-containing conjugated polymers have been synthesized and demonstrate photoluminescent, [39][40][41] photoconductive, [39] and photovoltaic properties, [42,43] examples of such devices based on metalcontaining polymers are limited. Furthermore, while varieties of polymers incorporating fullerenes into backbones, side-chains, and end-groups have been reported, [44] linear metallopolymers bearing fullerene groups are unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[303][304][305][306][307][308][309][310][311] The photoluminescence of a number of platinum polyacetylides has recently been reported by Kohler and coworkers. [306] By altering the conjugated spacers between the acetylide units in polymers 220-222, their triplet energy levels varied between 2.5 and 1.3 eV.…”
Section: Transition Metal Polyynesmentioning
confidence: 99%